GBE50 Attenuates Inflammatory Response by Inhibiting the p38 MAPK and NF-κB Pathways in LPS-Stimulated Microglial Cells. (24th March 2014) - He, Gai-ying; Yuan, Chong-gang; Hao, Li; Xu, Ying; Zhang, Zhi-xiong
Abstract : Overactivated microglia contribute to a variety of pathological conditions in the central nervous system. The major goal of the present study is to evaluate the potential suppressing effects of a new type of Ginko biloba extract, GBE50, on activated microglia which causes proinflammatory responses and to explore the underlying molecular mechanisms. Murine BV2 microglia cells, with or without pretreatmentof GBE50 at various concentrations, were activated by incubation with lipopolysaccharide (LPS). A series of biochemical and microscopic assays were performed to measure cell viability, cell morphology, release of tumor necrosis factor- α (TNF- α ) and interleukin-1 β (IL-1 β ), and signal transduction via the p38 MAPK and nuclear factor-kappa B (NF- κ B) p65 pathways. We found that GBE50 pretreatment suppressed LPS-induced morphological changes in BV2 cells. Moreover, GBE50 treatment significantly reduced the release of proinflammatory cytokines, TNF- α and IL-1 β, and inhibited the associated signal transduction through the p38 MAPK and NF- κ B p65 pathways. These results demonstrated the anti-inflammatory effect of GBE50 on LPS-activated BV2 microglia cells, and indicated that GBE50 reduced the LPS-induced proinflammatory TNF- α and IL-1 β release by inhibiting signal transduction through the NF- κ B p65 and p38 MAPK pathways. Our findings reveal, at least in part, the molecular basis underlying the anti-inflammatory effects of GBE50.